Exploring EFL Instructors’ Awareness and Perceptions of Using ChatGPT in Language Education - tayşı, eda; Hamamcıoğlu, Tuğçe; Gürkaya Dindar, Zerrin (LPPM Universitas Advent Indonesia, 2025)
Since it was first releasd in 2022, ChatGPT has rapidly become widespread as a well-known and widely used chatbot. This innovative tool has attracted interest from language teachers and researchers for its potential benefits in language learning and teaching. Despite this, there is very little scientific understanding of to what extent and how it is used for language learning and teaching purposes. To this end, this study aimed to investigate university level EFL instructors' awareness of ChatGPT's potential for language learning and teaching, and their perceptions of the advantages and disadvantages of using it. A questionnaire consisting of open-ended and closed-ended questions was administered to 153 EFL instructors working in different universities in Türkiye. The study found that although participants were aware of ChatGPT's capabilities and found it very useful for material development and lesson planning, they were concerned about inaccuracies, unreliable information, prompt difficulties, ethical issues, overreliance, and ineffective outputs. The findings of this study present several important implications for the effective integration of AI tools like ChatGPT into language instruction.